L’agglomération hospitalière de Cholet - Éric Morin (In Situ)
Like other hospitals during the nineteenth and twentieth centuries, the hospital at Cholet evolved according to a series of structuring facts: the legislative context, urban functions whether old or new, population growth, social demands for quality healthcare, professionalisation of the medical personnel, chronic financial difficulties... The hospitals of Cholet are a reflection of a fast-growing town, based on an active industrial sector, a sub-prefecture with barracks for army regiment, a town which, in the 1960s opted for a new hospital centre at the edge of town and left its old hospital in a state of abandonment. Where its real estate history is concerned, this old hospital is the result of local and national building agencies: figures in the administration, benefactors, the prefect, the ministry of War and the ministry of Health. The construction, in the 1830s, of a modern, hygienic building, specially for soldiers, is at the origins of the hospital agglomeration. The implantation of this building, its cost and its architectural forms will have a strong influence on subsequent additions. In a maze of intertwining buildings, the general plan is of a comb design, maintained up to the additions of 1912. But this triumph of economic reasoning was never seen as an evidence. Each time a new addition was planned, the proponents of the pavilion model (mostly medical professionals) defended this vision, but to no avail. Now, at the end of the twentieth century, the problem is one of how to convert a hospital site, in a state of abandonment. The municipal team has two ambitions: to use the space for the creation of teaching facilities and for the arts of the spectacle, and to enhance the existing heritage but not to the point of refusing all new build. It is now a site with a privileged place in the town, offering two visions of hospital heritage but, unfortunately, without any traces of its former hospital activities.